A Matrix Lie Superalgebra and Its Applications. (19th December 2013) - Han, Jingwei; Yu, Jing; He, Jingsong
Abstract : A matrix Lie superalgebra is established. As its applications, multicomponent super Ablowitz-Kaup-Newell-Segur (AKNS) equations and multicomponent super Dirac equations are constructed. By making use of supertrace identity, their super-Hamiltonian structures are presented, respectively.